2017
DOI: 10.1080/10942912.2017.1295987
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of Dracocephalum kotschyi essential oil obtained by microwave extraction and hydrodistillation

Abstract: Dracocephalum kotschyi essential oils obtained by hydrodistillation (HD), microwave-assisted hydrodistillation (MAHD), and solvent-free microwave extraction (SFME) were investigated by GC-FID (Gas Chromatography-Flame Ionization Detector) and GC-MS (Gas Chromatography-Mass Spectrometry). The percentage of oxygenated compounds was significantly increased from 62.52% in HD to 76.47% in MAHD, and 84.52% in SFME. Conversely, the monoterpene hydrocarbons were decreased from 30.84% in HD to 13.71% in MAHD, and 5.85%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Essential oil obtained from another Dracocephalum species, D. foetidumby , also showed inhibitory activity against most of the tested pathogenic bacteria and yeast strains with MIC values ranging from 26 to 2592 μg/mL; furthermore, the oil was found to exhibit significant antimicrobial activity against methicilin-resistant Staphylococcus aureus (MRSA) strains, indicating this oil has potential medical value [20]. Farimani et al [14] examined the antimicrobial activity of D. kotschyi essential oils against gram-positive ( Staphylococcus aureus ) and gram-negative ( Escherichia coli ) bacteria and found S. aureus was the most sensitive strain with an IC 50 value of 2 mg/mL. Zhang et al [19] tested the antimicrobial activity of the essential oil of D. heterophyllum against nine bacterial strains, one yeast, three fungi, and found that MIC values for bacteria, yeast, and fungi strains were 0.039–0.156, 0.156, and 0.313–2.500 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oil obtained from another Dracocephalum species, D. foetidumby , also showed inhibitory activity against most of the tested pathogenic bacteria and yeast strains with MIC values ranging from 26 to 2592 μg/mL; furthermore, the oil was found to exhibit significant antimicrobial activity against methicilin-resistant Staphylococcus aureus (MRSA) strains, indicating this oil has potential medical value [20]. Farimani et al [14] examined the antimicrobial activity of D. kotschyi essential oils against gram-positive ( Staphylococcus aureus ) and gram-negative ( Escherichia coli ) bacteria and found S. aureus was the most sensitive strain with an IC 50 value of 2 mg/mL. Zhang et al [19] tested the antimicrobial activity of the essential oil of D. heterophyllum against nine bacterial strains, one yeast, three fungi, and found that MIC values for bacteria, yeast, and fungi strains were 0.039–0.156, 0.156, and 0.313–2.500 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey of the chemical composition of essential oils produced by Dracocephalum plants revealed the presence of remarkable variations among their major constituents [12]. These oils were found to possess various biological activities such as antimicrobial [13,14,15,16,17,18,19,20], antioxidant [13,17,19,21,22,23], insecticidal [24,25], phytotoxic [26,27], cytotoxic [17], antispasmodic [28] and antinociceptive [29] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent polarity plays an important role in extraction of phenolic compounds. In this regard, methanol was a better solvent in extraction of phenolic compounds [71]. The quantity of luteolin in D. kotschyi was found to be 1061.005 μ g/g of dried plant.…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle of this type of extraction is azeotropic distillation (substances behave as if they were pure in relation to the boiling point), and to occur, a heating source, a container to place the vegetal biomass (for example, a volumetric flask), a condenser, and a decanter for collecting the oil and water mixture are necessary. HD is considered a multilateral method and, although simple, can be used in small or large industries because of its selectivity and low installation cost [20,23,24]. Hydrodistillation process is originated in alembics, however, since the third edition of the European pharmacopeia, its use along with the modified Clevenger system has been recommended, as this system enables the condensate recycling [20].…”
Section: Hydrodistillationmentioning
confidence: 99%